INTOLERANCE TO TOLERANCE - M. G. Pismanik (Концепт: философия, религия, культура, 2017)
The concept of tolerance as one of the basic values of humanism and the creative category of a truly correct cultural dialogue in the Russian language has been used in the humanities just since the end of the twentieth century. The concept is not identical with the Russian term tolerance, which in the main sense means one of religious virtues. Therefore, in the context of the implementation of the Public Policy Strategy, it is inadmissible to confuse these categories and the term. This article outlines the evolution of the principle of humanity, the related category of tolerance and their formation in the universe of modern Western culture. The necessity of applying tolerance as a methodological principle promoting the harmonization of ethnoconfessional relations in the post-Soviet society is substantiated. The article contains comments on the explication of categories in the well-known UNESCO document “Declaration of Principles of Tolerance”. Unfortunately, the category of tolerance was not included in the context of the program document “Implementation of the State National Policy” in force since the beginning of 2017. The author analyzes the factors that complicate the use of tolerance, the outlines of boundaries and the requirements of its creative and effective application in the ongoing practical implementation of the State National Policy Strategy.